Exploring Arab Folk Literature - Cachia, Pierre (Edinburgh University Press, 2022)
The character and range of Arab folk literature are investigated by Pierre Cachia in this collection of his pioneering essays in the field.Arranged into three sections, Cachia looks first at historical developments in the relationship between Arab folk literature and that of the elite, the gradual elaboration of certain genres, and the producers of folk literature. He then devotes a substantial section to the consideration of single or related texts. Finally he searches for evidence of social and cultural implications and for differences of attitudes of folk and elite towards sensitive issues.This book represents a major contribution to our understanding of Arab folk literature and will be of relevance to anyone with an interest in Arab literary creativity.Key FeaturesCollects Pierre Cachia's seminal work on Arab folk literature in one volumeIncludes two previously unpublished essaysExamines the history, texts, and social and cultural implications of the traditionFeatures a standardised transcription system based on pronunciation of the language - far more suited for oral forms of literature